Comparison of the effects of core stability and whole-body electromyostimulation exercises on lumbar lordosis angle and dynamic balance of sedentary people with hyperlordosis: a randomized controlled trial - Mohammad Hamzeh Shalamzari; Mohammad Amin Henteh; Alireza Shamsoddini; Ali Ghanjal (BMC, 2024)
Abstract Background Hyperlordosis is an excessive inward curvature of the lumbar spine that affects spinal function. The aim of this study was to compare the effects of core stability exercises (CSE), Whole-Body Electromyostimulation (WB-EMS), and CSE Plus on the Lumbar lordosis angle and dynamic balance in sedentary people with hyperlordosis. Methods In a parallel randomized controlled trial study, seventy five untrained male adults with hyperlordosis, recruited from clinics of sports medicine and corrective exercise centers in Tehran, were randomly assigned to four groups: CSE (n = 19), WB-EMS (n = 18), CSE Plus (n = 18), and control Group (CG) (n = 20). The CSE group performed Core stability exercises, the WB-EMS group followed a Whole-body electromyostimulation combined training protocol, and the CSE Plus group engaged in a combined program protocol (CSE with the WB-EMS vest), and the control group only participated in activities of daily living. Anthropometric parameters and outcomes, including the lordosis angle and dynamic balance, were assessed before and after a six-week training program. A flexible ruler was used to measure the angle of lordosis, and the Y balance test was employed to evaluate the dynamic balance. Results The results indicated that the lordosis angle improved in both the CSE and CSE Plus groups compared to the CG in the post-test (P = 0.017, P = 0.024). However, there were no significant differences observed between the other group pairs. Additionally, a significant difference in dynamic balance was found between the CSE Plus group and the CG in the post-test (P = 0.001), while no significant differences were observed between the other group pairs. Furthermore, within-group test results demonstrated that lumbar lordosis angle and dynamic balance variables significantly improved in the post-test compared to the pre-test stage (P < 0.05). Conclusions The two CSE and CSE Plus training protocols are effective as training methods for correcting certain parameters and physical deformities, including lumbar lordosis. Furthermore, the CSE Plus group demonstrated a positive impact on improving dynamic balance. Consequently, it is highly recommended that individuals with hyperlordosis can benefit from the exercises of the present study, especially CSE Plus exercises along with other rehabilitation exercises. Trial registration The trial was registered at Thai Clinical Trials Registry (TCTR20221004011, registration date: 04/10/2022).